World Order : Reflection on the Character of Nations and the Course of History - Kissinger, Henry (London Allen Lane an Imprint of Penguin Books, 2014)
Blending historical insight with prognostication, 'World Order' is a meditation from one of our era's most prominent diplomats on the 21st century's ultimate challenge: how to build a shared international order in a world of divergent historic perspectives, violent conflict, proliferating technology and ideological extremism.
Include Note and Index
Keywords: Geopolitics -- Security, International -- World politics -- International relations